2016
DOI: 10.7172/1733-9758.2016.21.2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Entrepreneurial Attitudes in Relation to Students of Economics and Non-Economics

Abstract: Keywords: entrepreneurial education, students' entrepreneurial attitudes, entrepreneurial competences, students of economics and non-economics. Submitted: 22.08.2016 | Accepted: 06.11.2016 Determinanty postaw przedsi biorczych studentów kierunków ekonomicznych i nieekonomicznych

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…In this research, effective entrepreneurship teaching received by students is able to stimulate the growing of motivation and attitude as essential learning features for accomplishing entrepreneurial assignments. This research finding supports the works of Khalili et al (2014), Farhangmehr et al (2016), and Jakubiak and Buchta (2016). It is also found that the higher students' entrepreneurial motivation make possible for them to reach the higher students' entrepreneurial attitude.…”
Section: Findings and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this research, effective entrepreneurship teaching received by students is able to stimulate the growing of motivation and attitude as essential learning features for accomplishing entrepreneurial assignments. This research finding supports the works of Khalili et al (2014), Farhangmehr et al (2016), and Jakubiak and Buchta (2016). It is also found that the higher students' entrepreneurial motivation make possible for them to reach the higher students' entrepreneurial attitude.…”
Section: Findings and Discussionsupporting
confidence: 81%
“…Knowledge learned and skills trained and developed during a semester taking the course is expected enable boosting students' motivation and attitude from inside becoming an entrepreneur (Raposo & do Paco, 2011). Practicality of entrepreneurship education is able to improve students' entrepreneurial competencies developed during taking the course and provide a positive impact on students' entrepreneurial motivation (Khalili et al, 2014;Farhangmehr et al, 2016;Jakubiak & Buchta, 2016). Previous research (Prodjosoesilo, 2005;Alain et al, 2006) revealed that there are relationships among students' entrepreneurial motivation and attitudes, entrepreneurship learning process, and students' concern in entrepreneurship education.…”
Section: Introductionmentioning
confidence: 99%
“…Those students who participate in an entrepreneurship education program tend to have high entrepreneurial motivations and are the most likely to start their own business (Solesvik, 2013). Khalili et al (2014), Farhangmehr et al (2016), and Jakubiak and Buchta (2016) also found that pragmatic entrepreneurship education assisted in improving the entrepreneurial competencies of students and developed their entrepreneurial motivations. On the other had, other researchers have found that entrepreneurship education does not impact the development of entrepreneurial motivations among students (Athayde, 2009; Oosterbeek et al, 2010).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Perceived behaviour increases when individuals perceive they have more resources and confidence (Lee & Kozar, 2005). The relationship between students entrepreneurial intention and entrepreneurship education using the theory of planned behavior is gaining the interest of academics and professionals (Izquierdo and Buelens, 2008;Sovitaris et al;. With the exception of Von Graevenitz et al;Oosterbeek et al;.…”
Section: Statement Of Problemmentioning
confidence: 99%